Literature review on the effect of landuse density and diversity on the passenger ridership of rail-based public transportation system - Mohamad Zulkifli, Siti Nur Awani; Jaafar Sidek, Mohd Farid; Kadar Hamsa, Abdul Azeez; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor (2015)
Government authorities in Malaysia are heavily investing on rail-based and road-based public transport system in and around Klang Valley (KV) including Kuala Lumpur. The heavy investment on rail transit is made with the expectation that it will increase the number of public transport patronage and thus decrease the use of private transport. Evidences from the literature suggest that Transit-oriented Development (TOD) is one of the planning concepts which facilitate the use of public transit system. The parameters such as density, diversity, and design are the key elements which should be properly planned for near transit stations to encourage the use of public transit. This paper describes, based on literature, the effects of land use density and diversity on passenger ridership of rail-based public transit systems. The data on density, diversity and passenger ridership from literature are analyzed in this paper.